Œ Case Files Vol. 01 - Ferracina, Simone (punctum books, 2021)
"Over the past ten years, Organs Everywhere (Œ) has promoted conversations that approach architectural design from the edges of the discipline - testing its boundaries, technologies, methods and (e)valuation systems, and keeping them unstable. It has valued transdisciplinary, speculative and irreverent explorations over strict publishing formats and academic purity, promoting a profanatory and open-ended ethos. Each issue has strung together disparate organs and limbs, activating precarious couplings and associations, and testing new metabolisms and assemblages. And so does the first volume of Œ Case Files continue its commitment to the making and unmaking of monsters, both by anthologising past contributions into fresh configurations and designs, and by combining them with entirely new articles and voices. Here, philosophers, designers, experimental architects, artists, science fiction writers, activists, and poets shift, expand and re-imagine notions of space, time, inhabitation, technology, knowledge, use, value and experience. A patchwork of essays, stories, design experiments, buildings, art installations, drawings, prose poems, photographs and speculative projects collide in the book, infecting simple disciplinary orthodoxies with doubt and potentials, uncertainty and hope - indecisive photons and softness; metatactility and haunted houses; neurodiversity and protocells; prosthetics, grease and darkness; post-human scenographies, software and GPS anklets; anthropocenic devices, paprika and synthetic biology."